Pengaruh Kecerdasan Emosional dan Budaya Organisasi pada Kinerja dengan Komitmen Organisasi (Management Analysis Journal, 2015)
The purpose of this study is to determine the influence of emotional intelligence, organizational culture, and Organizational Commitment on performance directly and indirectly that is mediated by Organizational Commitment. The population in this study were 126 employees in food, drink and cosmetic departemen in PT. Sido Muncul Herbal Medicine Industry. 96 people of them as data. Proportional Random Sampling of Probability Sampling technique was used for gathering the data. The method of data collection by quetionares. Data analysis using path analysis. The conclusion of this study are influence of emotional intelligence and organizational culture on organizational commitment, the influence of emotional intelligence and organizational culture on performance and organizational commitment mediate the relationship emotional intelligence and organizational culture on performance.